PENGUATAN BRANDING DAN AKSES PASAR UMKM DESA SOMAGEDE MELALUI PEMASARAN DIGITAL UNTUK MENDUKUNG EKONOMI BERKELANJUTAN - Hidayah, Asmi Ayuning; Hermadine, Nasywa Aulia; Yudhira, Salomo; Giovani, Nadya Ayu; Prapanca, Arico (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2025)
This community service program aims to strengthen the branding and market reach of micro, small, and medium enterprises (MSMEs) in Somagede Village, Banyumas Regency, through digital marketing strategies, particularly promotional video content. Based on a door-to-door survey involving 107 MSME actors, marketing and promotion were identified as the second-largest constraint after capital limitations, affecting 43.9% of respondents. Most MSMEs still rely on conventional marketing methods, resulting in limited market reach and low competitiveness. To address this issue, the program implemented the production of promotional videos and provided assistance in utilizing digital platforms. The activities involved selecting three MSMEs with high readiness for digital adoption, producing tailored promotional videos, and assisting one culinary MSME in registering as a ShopeeFood merchant. The results show that MSME partners gained promotional media ready for dissemination on social media platforms and increased digital literacy. This program demonstrates that simple and context-appropriate digital marketing interventions can enhance MSME competitiveness and contribute to local economic development.